The Success of Bounding Attachment Through The Process of Early Breastfeeding Initiation at Puskesmas Tawiri in 2022 - Mauren Pelamonia; Lili Farlikhatun (Sean Institute, 2023)
Health workers are obliged to carry out Early Breastfeeding Initiation of newborn babies to their mothers for at least 1 hour, if there are no medical contraindications. By doing Early Breastfeeding Initiation the inner bond between mother and baby will be closer, doing Early Breastfeeding Initiation also makes the baby have antibodies faster so as to prevent infectious deaths in babies. There are obstacles in doing bounding attachman, namely the lack of family support in providing peace between mother and baby, mothers who experience illness, babies who experience premature, sick babies, and physical defects so that after birth cannot be done Early Breastfeeding Initiation and the presence of unwanted presence. The purpose of this study was to determine the success of Bounding Attachment through the Early Breastfeeding Initiation Process at Tawiri Health Center. This study is an analytic survey with a retrospective cross-sectional design or design. The research was conducted at the Tawiri Health Center in October to December 2022. The sample in this study were 60 mothers who gave birth at the Tarwiri Health Center. The sampling technique used by non probability sampling with purposive sampling method. Bivariate analysis using SPSS chy - square test. The results of the study there is a relationship through the process of initiation of early breastfeeding by skin contact, work, economy, labor process and family and husband support with the success of Bounding Attachment at the Tawiri Health Center in 2022. And it is recommended to the health center to be able to carry out Early Breastfeeding Initiation for laboring mothers who have no indication during the delivery process so that bounding attachment is established.